Sensitive voltammetric method for determination of herbicide metribuzin using silver solid amalgam electrode - Janíková, Lenka; Šelešovská, Renáta; Rogozinská, Michaela; Tomášková, Markéta; Chýlková, Jaromíra (My University, 2016)
New sensitive voltammetric method for determination of triazinone herbicide metribuzin (MTZ) was developed employing polished and mercury meniscus-modified silver solid amalgam electrode (p-, m-AgSAE). MTZ yielded two reduction signals on both used working electrodes in acidic and slightly acidic media and the positively situated peak [at about -650 mV vs. Ag|AgCl|KCl (sat.)] was found suitable for further analytical measurements. The highest responses were recorded in Britton-Robinson buffer of pH 2 (p-AgSAE) or 3 (m-AgSAE). Various voltammetric techniques like cyclic, linear sweep, and differential pulse voltammetry were used for examination of the voltammetric behavior of MTZ. Parameters of differential pulse voltammetry were optimized and low detection limits were reached (LODm-AgSAE = 6.0 x 10(-8) mol dm(-3) and LODp-AgSAE = 7.5 x 10(-8) mol dm(-3)). Moreover, excellent repeatability of determination and measurements as well was confirmed by low values of relative standard deviations of five repeated determinations [RSD (5) a parts per thousand currency sign 6.0 %] and of 11 repeated measurements [RSD (11) a parts per thousand currency sign 4.5 %], respectively. Finally, practical applicability of newly proposed methods was verified by the analysis of spiked tap and river water and by determination of MTZ in pesticide preparation with excellent results. All the obtained results were compared with those gained for classic mercury electrode.
Citlivá voltametrická metoda stanovení herbicidu metribuzinu s využitím stříbrné pevné amalgámové elektrody
Keywords: Electrochemistry; Voltammetry; Herbicide; Metribuzin; Silver solid amalgam electrode; Hanging mercury drop electrode; Elektrochemie; voltametrie; herbicidy; metribuzin; stříbrná pevná amalgámová elektroda; visíc rtuťová kapková elektroda